A new species of the genus Smicromyrme THOMSON, 1870 (Hymenoptera: Mutillidae) from India - Terine, Joshua B.; Kumar, Girish P. (Zootaxa, 2023)
Smicromyrme (Eremotilla) williamsi Terine & Girish Kumar, sp. nov. is described based on a female specimen from Kerala, Southern India. A modified key to the S. coromandelica species-group (females only) is given.